Best Answer

you are saying

t + t + t + 3t = 6 + 4t

if soo..

you must combine like terms... meaning combine all the "t's" on the left hand side of the equal side. when you add the "t's" together... you will get "6t"

so now your problem will look like this:

6t = 6 + 4t

since you want "t" by itself... you must bring over the positive "4t" to the left hand side. To do that you must subtract 4t to both sides.

so it should look like this:

2t = 6

from there you must divide 2 to both side of the equation cause you want "t" by itself. when you do that... your answer will be

t = 3

Q: T plus t plus t plus 3t equals 6 plus 4t?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

t+8 = 2-3t add 3t to both sides: 4t+8 = 2 take 8 away from both sides: 4t = -6 divide both sides by 4: t = -6/4 = -3/2

t = -11/10

Yes and t = 1 in both equations

4t - 6 = 4*(-6) -6 = -24 -6 = -30

20t

Related questions

t+8 = 2-3t add 3t to both sides: 4t+8 = 2 take 8 away from both sides: 4t = -6 divide both sides by 4: t = -6/4 = -3/2

3t+11 = 29 3t = 29-11 3t = 18 t = 6

S = 3 st + 3t = 6 st = 6 - 3t s = (6 - 3t)/t = 6/t - 3

4+3t = 22 3t = 22-4 t = (22-4)/3 t = 6

t = -11/10

Yes and t = 1 in both equations

4t - 6 = 4*(-6) -6 = -24 -6 = -30

3t - 15 = -9 3t - 15 (+15) = -9 (+15) 3t = 6 3t (/3) = 6 (/3) t = 2

20t

10t=6t+24 -6 -6 4t=24 4 4 1=6 t=6

4t = 24 Therefore t = 24/4 t = 6

2t + 3 = -9Subtract 3 from each side:2t = -12Divide each side by 2:t = -6======================-3t - 7 = (-3)(-6) - 7 = +18 - 7= 11.